REGIONAL REGULATION CONCERNING SPORTS ORGANIZING: IS IT NECESSARY FOR REGENCY IN INDONESIA? - Suharso, Suharso; Budiharto, Budiharto (Varia Justicia, 2019)
As regional autonomy, a Regency has an obligation to organize government affairs. In addition, it also has the option of attribution authority in accordance with the constitution. The Regional Government organizes the field of government affairs that can foster healthy human resources. One of its authorities is the provision of sports facilities. This study aims to analyze the urgency of the Regulations on Organizing Sports. This research method is Legal Research through a qualitative approach by examining regulations/laws related to the authority of regional autonomy in organizing sports facilities. The results show that the formation of a Regional Regulation on the Implementation of Sports is prepared by taking into account the rules for the formation of legislation mandated by Law Number 12 of 2011 concerning Formation of Legislation. Thus the regulations decided can be implemented and in accordance with applicable legal provisions.